(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article is part of a research related to the history of books and reading practices in Mexico at the end of the viceroyalty. The trajectory of Ana Manuela Muñiz Sánchez de Tagle, the “library” that was able to form in the late eighteenth century and the analysis of its books, provide insight into the interests and literary tastes of women from the New Spain and how they could access to reading materials, but at the same time, serves to stimulate a debate on the concept that had the people from the New Spain of their books collections and the sense historians have given now. On the other hand, the study analyzes the mechanisms of formation of a feminine bookstore in a provincial town; the way it was organized by the owner, the spaces and practices of reading they used to use, the content of the books, as well as the intellectual world they represented. The essay ends with the final years of Manuela Muniz.